Effectiveness of A Coping Style- related Instructional program on Self - Care of Patients with Diabetes Mellitus Type II at Endocrinology and Diabetes Center in Al-Basra City - Rajaa Ibrahim Abed; Saja’ Kareem Jassim (Indian Journal of Forensic Medicine & Toxicology, 2021)
Methodology: A descriptive analytic (quasi – experimental) design. Sample composed of (60) patients were divided into two groups study and control group, (30) patients in each one. Results: The study findings Shows that participants’ age group at a level (46-65 years) were (67.7%) of the study group, and (56.7%) of the control group. (56.7%) of the study group were male, while (53.3%) of the control groups were female. The study also confirms that the effectiveness of a Coping style related instructional program on Self - Care of Patients with Diabetes Mellitus Type II at Endocrinology and Diabetes Center in Al-Basra City, Iraq.Conclusion : The study concludes that A coping style-related instructional program is effective to enhance diabetes patients’ self-care activities, knowledge, and coping style among patients with T2DM. This conclusion is based on the result of our study that reveals significant differences between pre-intervention and post-intervention. Recommendations: Improve knowledge and self-care activities of patients with T2DM, by using our study guidelines.. Encourage the health care provider to improve diabetic patients’ self-care activities and focusing on all domain aspects of self-care.